Genomic Insight Into the Population Admixture History of Tungusic-Speaking Manchu People in Northeast China - Zhang, Xianpeng; He, Guanglin; Li, Wenhui; Wang, Yunfeng; Li, Xin; Chen, Ying; Qu, Quanying; Wang, Ying; Xi, Huanjiu; Wang, Chuan-Chao; Wen, Youfeng (Frontiers in Genetics, 2021)
Manchu is the third-largest ethnic minority in China and has the largest population size among the Tungusic-speaking groups. However, the genetic origin and admixture history of the Manchu people are far from clear due to the sparse sampling and a limited number of markers genotyped. Here, we provided the first batch of genome-wide data of genotyping approximate 700,000 single-nucleotide polymorphisms (SNPs) in 93 Manchu individuals collected from northeast China. We merged the newly generated data with data of publicly available modern and ancient East Asians to comprehensively characterize the genetic diversity and fine-scale population structure, as well as explore the genetic origin and admixture history of northern Chinese Manchus. We applied both descriptive methods of ADMIXTURE, fineSTRUCTURE, FST, TreeMix, identity by decedent (IBD), principal component analysis (PCA), and qualitative f-statistics (f3, f4, qpAdm, and qpWave). We found that Liaoning Manchus have a close genetic relationship and significant admixture signal with northern Han Chinese, which is in line with the cluster patterns in the haplotype-based results. Additionally, the qpAdm-based admixture models showed that modern Manchu people were formed as major ancestry related to Yellow River farmers and minor ancestry linked to ancient populations from Amur River Bain, or others. In summary, the northeastern Chinese Manchu people in Liaoning were an exception to the coherent genetic structure of Tungusic-speaking populations, probably due to the large-scale population migrations and genetic admixtures in the past few hundred years.